Being and Becoming: the Implications of Different Conceptualizations of Children and Childhood in Education - Jingyi Huang (Canadian Society for Studies in Education, 2019)
How to conceptualize children and childhood are intrinsic to the ways of understanding education. The 'becoming' child is seen as an opposite or negative form of adults while the 'being' child is recognized as a social actor with the ability as well as rights to actively participate in its own life and in those of others. However, in addition to the problems of each discourse, such a dyad also leads to a separation of fundamental education factors. With reference to the Interpretative Reproduction Model and the concept of time, this paper discusses an alternative perspective on children and childhood that views the child as the 'human becoming and being' concurrently, coupled with its associated implication on education. By doing so, the author hopes to provide a platform facilitating adult professionals, pre-service or in-service teachers, to reflect upon their attitudes towards students and the ways of understanding education.